Inhibitory effect of the glucosinolate-myrosinase system on Phytophthora cinnamomi and Pythium spiculum - Francisco T. Arroyo; Rocío Rodríguez Arcos; Ana Jiménez Araujo; Rafael Guillén Bejarano; María José Basallote; Carmen Barrau (Plant Protection Science, 2019)
Glucosinolate extracts from sprouts of common Brassica nigra, B. juncea cv. Scala, B. carinata cv. Eleven, and Sinapis alba cv. Ludique were analysed by reversed phase high-performance liquid chromatography-diode array detection-mass spectrometry. The effect of the glucosinolate-myrosinase system on in vitro mycelial growth of Phytophthora cinnamomi Rands and Pythium spiculum B. Paul was assessed. Likewise, sinigrin and sinalbin monohydrate commercial standards were also tested. The extracts from B. carinata, which contained 159 mmol/g plant DW equivalent (85% sinigrin, 5% gluconapin, and 3% glucotropaeolin), were the most effective against Phytophthora and Pythium isolates used in this study. However, the extract from S. alba, which contained 1 180 mmol/g (100% sinalbin), did not inhibit the mycelial growth of the isolates tested. The use of the glucosinolate-myrosinase system provides important additional information to advance in the implementation of field application of brassicaceous amendments for the control of soil-borne pathogens.